The Trends in Opioid Use in Castile and Leon, Spain: A Population-Based Registry Analysis of Dispensations in 2015 to 2018 - Herrera-Gómez, Francisco (J Clin Med, 2019)
Opioids are driving-impairing medicines (DIM). To assess the evolution and trends of opioid analgesics use between 2015 and 2018 in Castile and Leon (Spain), a population-based registry study was conceived. The length of opioid use and its concomitant use with other DIMs were studied. Analyses were done considering age and gender distributions. Adjusted consumption for licensed drivers is also presented. Of the 5 million dispensations recorded between 2015 and 2018, opioid analgesics were dispensed to 11.44% of the general population and 8.72% of vehicle drivers. Increases among daily users (2.6 times higher) and chronic users (1.5% higher) were noted, supporting the overall increase in opioid use (1.5%). The use of multiple drugs including other DIMs was a common finding (mean ± SD, 2.54 ± 0.01). Acute use (5.26%) and chronic use (3.20%) were also frequent. Formulations combining opioid analgesics with nonopioid analgesics were preferred. The use of opioids increased in Spain between 2015 and 2018. Concomitant use with other DIMS especially affects women and the elderly. Frequent use of opioid analgesics with other DIMs is a serious problem for drivers and increases the risk of accidents. Promoting safe driving should be a main objective of health authorities, to be achieved by developing and implementing educational activities for healthcare professionals and patients.